Attachment Style and Dark Triad Personality as Predictors of Ghosting Behavior in Online Dating Contexts - Sukri, Sri Wahyuni; Noviekayati, IGAA; Santi, Dyan Evita (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Millennials and Generation Z are the age groups that dominate the use of digital dating applications. In these generations, building interpersonal relationships is relatively easy, including interactions through digital platforms. The phenomenon of ghosting—defined as the sudden termination of communication without explanation—frequently emerges in this context. This study aims to explore the relationship between attachment style and dark triad personality traits on ghosting behavior among dating application users. The research employed a quantitative approach with a path analysis method. The sample consisted of 254 emerging adults who use dating applications, selected through purposive sampling techniques. The results showed that attachment style had a significant negative effect on ghosting behavior (β = -0.408; p < 0.05), indicating that individuals with secure attachment are less likely to engage in ghosting. Conversely, dark triad personality traits had a significant positive effect on ghosting behavior (β = 0.548; p < 0.05), where the dimensions of Machiavellianism, narcissism, and psychopathy increased the likelihood of ghosting. Regression analysis revealed a significant simultaneous contribution (F = 471.850; p < 0.05), with the independent variables explaining 79% of the variance in ghosting behavior. These findings indicate that attachment style and dark triad personality traits play an important role in shaping ghosting behavior in the digital era. This study can serve as a basis for developing psychological interventions to improve the quality of interpersonal relationships in the context of dating applications.